Analysis of Islamic Socio-Political and Cultural Meneutics of the Limo Migo Community in the Dalung Bojong inscription of East Lampung - Muhammad Saidun Anwar; Choirudin Choirudin; Mispani Mispani; Leli Fertiliana Dea; Ahmad Muslimin (Medina-te : Jurnal Studi Islam, 2020)
The study aims to contextualize the content of the inscription of DalungBojong of East Lampung in the modern era with Fazlur Rohman’s hermeneutical approach. The data were taken from interviews with the main witness, Haji Hasanuddin (Pangiran Betaro Rajo III) as the author and the writer of the inscription DalungBojong and Mr. Hasan al-Basri (Pangiran Sebuwaias the traditional leader of Bojong Village). Dalung Bojong inscription is an archaeological evidence of the strong influence of Banten over Lampung as its territory. The relationship patterns depicted in the inscription are: First, the pattern of political relations in determining all decisions is based on the Sultan's decree. Second, the pattern of economic relations. Banten as a commercial center between nations has an interest in Lampung as an area that produces a lot of agricultural products to meet the needs of trading commodities. Third, the patterns of religious and cultural relations, the patterns of political and economic relations that are formed, and the socio-cultural contacts also occured. The Sultanate of Banten in Islamizing the Pugung people gave birth to many socio-political and cultural dynamics. Queen Pugung, who has principles, never gave up before the war. However, Queen Pugung realized that it was impossible to do war against his daughter-in-law. Finally, Queen Pugung made a circle rule. Those who do not follow the KeratuanPugung rules and choose to convert to Islam must leave the circle (the Pugung area) to the nearby areas of Pugung which became the forerunners of the Sekampung Limo Migo community.